PERIPHERAL NERVE BING-NEEL SYNDROME. Issue 11 (14th October 2015) - Carr, Aisling; D'Sa, Shirley; Arasaretnam, A; Boyd, K; Johnston, R; Jaunmuktane, Zane; Brandner, Sebastian; Marafioti, T; Koltzenburg, Martin; Lunn, Mike
Abstract : Background: Bing-Neel syndrome (BNS) is a rare manifestation of Waldenstrom's Macroglobulinaemia (WM) due to direct infiltration of the central nervous system. Isolated peripheral nerve infiltration has not been described but as the blood-nerve-barrier has similar characteristics to the blood-brain-barrier, CNS-penetrating chemotherapy would be required. Case: A 43 year-old man was diagnosed with WM after presenting with constitutional symptoms; IgMk paraprotein (34.6 g/L) and lymphoplasmacytoid cells in the bone marrow. He received R-CVP (Rituximab, Cyclophosphamide, Vincristine, and Prednisolone) with good partial haematological response and minimal distal sensory vincristine-related neuropathy. Ten months later he developed a rapidly progressive, symmetric sensorimotor deficit in all four limbs with impairment of walking and hand clumsiness, MRC sum score=61/70. Electrophysiology showed a non-length dependant axonal neuropathy with patchy slowing. Sural nerve biopsy revealed a patchy infiltrate WM cells. He tolerated 4 cycles of blood-nerve-barrier penetrating multi-agent chemotherapy, IDARAM (idarubicin, dexamethasone, cytosine arabinoside, methotrexate, cytosine arabinoside plus intrathecal methotrexate). A marked improvement was seen during treatment and by 3 months later MRC score was 70/70. No electrophysiological difference was detectable at this stage. Discussion: Peripheral BNS is not a recognised neurological manifestation of WM but with appropriate treatment a good outcome may be achieved.